Forest Fire - Szmyt, Janusz (IntechOpen, 2018)
This book concerns the different aspects of forest fires, the impact of fire on both forest resources (e.g. forest cover) and communities that use different forest functions. Therefore, forest fires have their environmental, economic and social consequences, and none of them is less important. Forest fires can be caused by both natural forces and anthropogenic factors, and in the latter case, it is extremely interesting to profile the potential arsonist. Forest fires may also cause conflicts, stronger or weaker, in local communities that have been using forests for years. These conflicts can be solved both by gradually changing the law itself and through education at the local level. Not less important is the ability to detect fires early, which can be helped by the development of modern technologies. In limiting the effects of forest fires, it may also be helpful to develop mathematical models that indicate various factors affecting the possibility of a fire or affecting the rate of its spread. Not less important is the attempt to assess the direction of forest regeneration after the fire has ceased, in understanding what the help of modern technology is. These aspects of forest fire are the subject of this book. I realize, however, that the contents in it can only be an incentive for the reader to learn more, in an interesting aspect. I assume that this book will be valuable to researchers as well as students who are interested in different aspects connected to forest fires, not only from the ecological point of view but also from the social one. Both are extremely important in future forest protection and sustainable use of forest by local communities.